2021
DOI: 10.4236/mrc.2021.102004
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Mesh-Type Fe-Pd/γ-Al<sub>2</sub>O<sub>3</sub>/Al Bifunctional Catalysts for Electro-Fenton Degradation of Rhodamine B

Abstract: A novel Fe-Pd bifunctional catalyst supported on mesh-type γ-Al 2 O 3 /Al was prepared and applied in the degradation of Rhodamine B (RhB). The monolithic mesh-type Fe-Pd/γ-Al 2 O 3 /Al bifunctional catalyst could be separated from the solution directly and could synthesize H 2 O 2 in situ. The characterization results showed that Fe could improve the dispersion of Pd 0 , and the electronic interactions between Pd and Fe could increase the Pd 0 contents on the catalyst, which increased the productivity of H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Li et al 26 reported that Pd–Sn nanocrystals stimulated a noticeable enhancement in H 2 O 2 production due to their inhibition of decomposition and hydrogenation of H 2 O 2 . In our previous work, 27 a Fe–Pd bifunctional catalyst was successfully designed and applied in the EF degradation of Rhodamine B. Not only could Fe slightly inhibit OO bond dissociation to promote H 2 O 2 production on Pd, but it could also degrade Rhodamine B through Fenton reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 26 reported that Pd–Sn nanocrystals stimulated a noticeable enhancement in H 2 O 2 production due to their inhibition of decomposition and hydrogenation of H 2 O 2 . In our previous work, 27 a Fe–Pd bifunctional catalyst was successfully designed and applied in the EF degradation of Rhodamine B. Not only could Fe slightly inhibit OO bond dissociation to promote H 2 O 2 production on Pd, but it could also degrade Rhodamine B through Fenton reaction.…”
Section: Introductionmentioning
confidence: 99%